Combined effect of applied equipment and formulation of pesticide on in relation to harmful effects for honeybees in Libya - Jabail, Farg A.; Al-Sherif, A. Ahmed (2011)
In Elhamronia Zone, Tripoli, Libya, field and laboratory studies were conducted in summer 2008 to investigate drift of Cyanophos applied on potato fields onto adjacent maize plants. Drift deposits of Cyanophos was determined as pg/kg maize leaves. The determinations were conducted on leaves of maize grown at various distances from the edge of the treated potato fields (i.e. 5, 8, 14. up to 51 m). Distances traveled by drift in the 1st spray were farther than those of the 2nd spray. This result could be easily explained on the basis that wind speed was higher in 1st spray (wind speeds were 3.8 and 2.6 km/hr during time of application in the 1st and 2nd sprays, respectively). The farthest distance within maize field reached by drift was observed for the dust application followed by micron UL V A and mistblower spraying ++(the distances were 26,35 and 44 m in the first spray when using the mistblower, micron ULVA and the mistblower as a duster, respectively). The corresponding values of drift deposits were 18.5, 13.6 and 28.4 pg/kg maize leaves, respectively. The potential drift emitted by micron ULVA compared with that of mistblower may be due to the smaller droplets of the former sprayer. Drift of Cyanophos released by each of the tested equipment caused 100% mortality of honeybees placed at the distances 5 and 8 m from the edge of treated potato field. For the dust application, 100% mortality was observed at longer distances (14 and 17 m). The study suggests that buffer zones (no spray zones) have to be established downwind of the treated field to avoid environmental contamination due to off-target deposition of pesticide drift. The model and specifications of these zones depend variably on quality of spray, release height, wind speed and other factors. Other measures of drift mitigation have to be considered.
Includes references.
Summary in Arabic.
1
Keywords: Pesticides -- Environmental aspects; Honeybee -- Effect of pesticides on